A SYSTEMATIC REVIEW OF THE NEOLIBERAL HOUSING POLICY: AN INTERNATIONAL PERSPECTIVE - Rehman, ABDUL; Anak Tedong, Peter Aning; MD DALI, MELASUTRA (Journal of Surveying, Construction and Property, 2023)
In recent years, there has been a burgeoning discourse surrounding the influence of neoliberalism on housing policy, governance, and affordability. The evolution of housing policies has coincided with the global ascent of neoliberal principles. The ideological underpinnings of neoliberalism, characterized by a focus on private property rights, unrestricted flow of capital, reliance on self-regulation in free markets, and the process of deregulation, exert a substantial impact on the trajectories of housing policies and urban governance in numerous countries. This article conducts a comprehensive review of the existing literature on housing policy and neoliberalism, adhering to the PRISMA guidelines and systematic review statements, utilizing ’housing policy and neoliberalism’ as keywords. The objective of this study is to identify prevalent research themes within the realm of affordable housing and neoliberalism. The primary themes influencing affordable housing policy, as indicated by the results, encompass privatization, deregulation, and privatization once more. Subthemes within this context include the privatization of public housing, the elimination of zoning restrictions or the adoption of inclusionary zoning, and the adoption of a market-driven approach. The outcomes of this study aim to streamline existing research, offering valuable insights for future research endeavors and aiding relevant stakeholders in formulating effective affordable housing policies and enhancing the governance of housing delivery mechanisms.